Poor perinatal care practices in urban slums: Possible role of social mobilization networks - Khan Zulfia; Mehnaz Saira; Khalique Najam; Ansari Mohd; Siddiqui Abdul (Wolters Kluwer Medknow Publications, 2009)
Background: Making perinatal care accessible to women in marginalized periurban areas poses a public health problem. Many women do not utilize institutional care in spite of physical accessibility. Home-based care by traditional birth attendants (TBA) is hazardous. Inappropriate early neonatal feeding practices are common. Many barriers to perinatal care can be overcome by social mobilization and capacity building at the community level. Objectives: To determine the existing perinatal practices in an urban slum and to identify barriers to utilization of health services by mothers. Study Design: This is a cross-sectional descriptive study. Setting and Participants: The high-risk periurban areas of Nabi Nagar, Aligarh has a population of 40,000 living in 5,480 households. Mothers delivering babies in September 2007 were identified from records of social mobilization workers (Community Mobilization Coordinators or CMCs) already working in an NGO in the area. A total of 92 mothers were interviewed at home. Current perinatal practices and reasons for utilizing or not utilizing health services were the topics of inquiry. Statistical Analysis: Data was tabulated and analyzed using SPSS 12. Results: Analyses revealed that 80.4% of mothers had received antenatal care. However, this did not translate into safe delivery practices as more than 60% of the women had home deliveries conducted by traditional untrained or trained birth attendants. Reasons for preferring home deliveries were mostly tradition (41.9%) or related to economics (30.7%). A total of 56% of the deliveries were conducted in the squatting position and in 25% of the cases, the umbilical cord was cut using the edge of a broken cup. Although breast-feeding was universal, inappropriate early neonatal feeding practices were common. Prelacteal feeds were given to nearly 50% of the babies and feeding was delayed beyond 24 hours in 8% of the cases. Several mothers had breastfeeding problems. Conclusion: Barriers to utilization of available services leads to hazardous perinatal practices in urban slums.